A study of political communication in social media: signature date a case study of UiTM's Rembau Masscom student perception / Nurul Diyana Syuhada Muhamad Areff - Muhamad Areff, Nurul Diyana Syuhada (2018)
Social media can be describes as a technologies that allow users to socialize with one and another such as Facebook, Google+, Twitter, Instagram, Pinterest and many more. Nowadays, social media function has changes and had attract politician to highlight themselves and centralize the party politician. Political communication can be understand by political speech, ideology and can also be viewed as the practice of using language to persuade and influence voters using social media. This study is to determine the UiTM's, Campus Rembau masscom student perception on political communication in social media. The researcher has distributed the questionnaire to 40 respondent from Faculty Communication and Studies and later did analysis upon the collect data. The researcher also hope that this research may be helping to other researcher upon the same subject that is political communication in social media.